Linguistic Units Determining the Semantic-Informational Field of the Basic Concept “Happiness” in M. Zhumabayev’s Works - Baltabaeva Ж.Қ.; Biyazdykova Ә.Ә. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
The article sets out informational content fields that form the basic concept of “happiness” in the verses of Magzhan Zhumabaev, analyzes the language models that define them, and the cognitive structure of language units. When analyzing the poems of M. Zhumabaev, ten semantic-informational fields were identified that form the basic concept of “happiness”. Linguistic units and cognitive structures are systematically analyzed and interpreted as semantic information fields that form this concept. During the analysis, the poet’s personal vision of the poet’s happiness, his description, his own style was revealed. The picture of the political life of the same period, the state of society, the fate of the Kazakh people at the beginning of the twentieth century was clearly reflected in poetic poems. They are especially evident in the concept of happiness.